Competitive and Cooperative Instructions In Learning English - Umida Hakimova (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
This article examines the dynamics of competitive and cooperative learning environments within the framework of TESOL practices. The author reflects on personal experiences as both a learner and teacher while drawing on social interdependence theory and empirical research. Competitive learning fosters anxiety and lowers intrinsic motivation by emphasizing individual performance frequently at the expense of others and it is often characterized by negative interdependence. Cooperative learning, on the other hand, encourages students to be positively interdependent, which improves their ability to work together, their intrinsic motivation, and their language proficiency. The current article explores the implications for creating encouraging and productive learning environments in TESOL classrooms by looking at real-world applications of both strategies